SAT0547 The influence of osteoarthritis on clinical, laboratory and ultrasound parameters of patients with early rheumatoid arthritis. (15th June 2017) - Serban, T; Satulu, I; Vutcanu, O; Milicescu, M; Mihai, CM; Bojinca, M
Abstract : Background: Osteoarthritis (OA) and rheumatoid arthritis (RA) are not infrequent in the general population. The two pathologic entities can overlap and the presence of OA can interfere with the evaluation of patients with RA. Objectives: This study aims to evaluate the possible impact of OA on the clinical, laboratory and ultrasound parameters currently evaluated in patients with early RA (ERA). Methods: We have evaluated the data obtained from patients with ERA referred to our Early Arthritis Research Center (EARC). Only data from patients who fulfilled EULAR/ACR 2010 criteria for RA (1) and had a symptom duration of less than 12 months were analyzed. 43 patients were diagnosed with ERA in the EARC between 2012 and 2016 and were enrolled in this study. Patients were evaluated at baseline and after 12 months. All patients underwent clinical examination, laboratory tests and ultrasound (US) examination. For the US examination we have calculated the score proposed by Naredo et al. considering that this simplified US score includes the evaluation of the hand and knee. (2) Results: There was a clear predominance of women (62.8%). The mean age was 55.47±13.71 years. At baseline, 21 patients (48.8%) were diagnosed with OA. 15 patients (34.9%) presented hand OA and 9 patients (20.9%) presented knee OA. Hand OA didn't influence the values of DAS28, SDAI, patient's and physician's visual analogue scale (VAS) or ultrasound scores (p>0.05). For patients with knee OA, significantly higher values for DAS28 were observed at baseline (p=0.018) and were maintained significantly higher after 12 months of observation (p=0.031). All the other parameters were not influenced by the presence of knee OA (p>0.05). The median value and interquartile range for lab tests and for disease activity indices are shown in Table 1 . Conclusions: Significantly higher values of DAS28 were observed in patients with ERA who associated knee OA, while the values of SDAI were not influenced, suggesting that SDAI may be superior to DAS28 in evaluating patients with ERA and knee OA. Not the same tendency was observed in patients with ERA and hand OA. The values of patient's VAS were not influenced by the presence of hand or knee OA suggesting that these types of OA do not influence the patients' perception of the disease activity. Moreover, the values of ultrasound scores were not influenced by the presence of OA. References: Aletaha D et al. Arhritis Rheum. 2010;62:2569–2581. Naredo E et al. Clin Exp Rheumatol. 2005;23:881–884. Disclosure of Interest: None declared